Advancements in Nano-Mediated Biosensors: Targeting Cancer Exosome Detection - Tripathi A.D.; Labh Y.; Katiyar S.; Chaturvedi V.K.; Sharma P.; Mishra A. (My University, 2025)
Cancer-derived exosomes, a subset of extracellular vesicles, carry vital information about tumor progression, metastasis, and drug resistance, making them attractive targets for cancer diagnostics and therapeutics. The identification of these cancer exosomes with high sensitivity and specificity has enormous promise for early diagnosis and prognosis. Nano-mediated biological sensors are establishing themselves as innovative techniques for detecting cancer exosomes based on the distinctive physicochemical attributes of nanomaterials to improve detection sensitivity and specificity. This article presents an overview of the recent developments in nano-mediated biosensors directed particularly toward the detection of cancer exosomes. The development of ultrasensitive sensors has been enhanced by using nanomaterials such as magnetic nanoparticles, quantum dots, and gold nanoparticles. Surface modifications of these nanomaterials by conjugating the cancer-specific antibodies or aptamers facilitate target recognition and binding of cancer exosomes, thus increasing the sensitivity of detection. This review compiles different detection techniques, including SERS, Electrochemical, SPR, Chemiluminescence, and Fluorescence-based biosensor detection, in combination with different nanomaterials that are currently being researched or utilized as biosensors. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.